'Abd al-Rahman b. 'Amr al-Awza'i - Judd, Steven C. (Simon and Schuster, 2019)
‘Abd al-Rahman b. ‘Amr al-Awza‘i (c.707–774) was Umayyad Syria’s most influential jurist, part of a generation of scholars who began establishing the first formal structures for the preservation and dissemination of religious knowledge. Following the Abbasid revolution, they provided a point of stability in otherwise unstable times. Despite his close ties to the old regime, al-Awza‘i continued to participate in legal and theological matters in the Abbasid era. Although his immediate impact would prove short-lived, his influence on aspects of Islamic law, particularly the laws of war, endures to this day.
Google-Books-ID: LknmDwAAQBAJ
Keywords: Biography & Autobiography / Historical; History / General; History / Middle East / General; Law / Islamic; Religion / History; Religion / Islam / General; Religion / Islam / Theology; Social Science / Islamic Studies; dept.his

The Saints of Progress: A History of Coffee, Migration, and Costa Rican National Identity - Kordick, Carmen (The University of Alabama Press, 2019)
"This work narrates the development of a historically remote–although internationally celebrated–coffee-growing region from the early 19th century through to the first decade of the 21st century. It considers the nation-building process from the margins to question traditional scholarly works that have reproduced, rather than deconstructed, Costa Rica's exceptionalist national mythologies that imagine this isthmian republic as Central America's 'white,' democratic, nonviolent, and egalitarian republic. The book recognizes that even though Costa Rica's exceptionalist rendition draws on some undeniable realities, it thoughtfully considers the origins, applicability, and longevity of the different elements of this exceptionalist master narrative. In particular, it suggests the mythology emerged during the Cold War, as revolution, civil war, military dictatorship, and state violence plagued much of Central America. In this same period, Costa Rica not only retained a relatively stable democratic system, but policymakers eliminated the standing army in 1948. This widely embraced and celebrated historical narrative, however, distorts as much as it illuminates the experience of contemporary and historical actors"–
Keywords: Coffee industry; Costa Rica; Costa Rica; History; Political aspects; dept.his

Sabbatical report on Contesting the Origins of the First World War - Paddock, Troy R. E. (2019)
Dr. Paddock spent the year completing a book and revising an article.
Keywords: dept.his; faculty_collection; sabbatical_report

Nightmare Factories The Asylum in the American Imagination - Rondinone, Troy (Johns Hopkins University Press, 2019)
Keywords: History; History; Asylums; Psychiatric hospitals; United States; dept.his; faculty_collection

To the editors - Forbes, R.P.; Mintz, S.; Stauffer, J. (American Historical Review, 2019)
Keywords: dept.his; ⛔ No DOI found

Intellectuals and “democratic elements”: A distrusted underclass - Lee, T.-L. (Hum. Rights in the People's Repub. of China, 2019)
As the targets of numerous campaigns, intellectuals have sustained mental torment and physical suffering on a large scale. Like the deprivation of human rights for biological and genetic reasons in other lands or other ages, Chinese intellectuals were destined to suffer abridgement of their human rights in the People’s Republic of China for political and ideological reasons. The term “intellectuals” refers to all those who have had a middle school/higher education and those with similar educational levels. Included in the ranks of intellectuals were members of the so-called democratic parties. These people, never large in number, were mostly well educated and well known in intellectual circles. The Cultural Revolution will be long remembered by intellectuals not only as a period of continued mental torment from the earlier days, but more particularly as a period of the most cruel physical abuses in human history. Intellectuals, deprived of their most precious human rights, continue to exist in mainland China as an underclass. © 1988 by Taylor & Francis. All rights reserved.
Journal Abbreviation: Hum. Rights in the People's Repub. of China
Keywords: dept.his

Red guards and political dissidents (I): Tools of violence and power struggle - Lee, T.-L. (Hum. Rights in the People's Repub. of China, 2019)
In 1966, Mao Zedong launched the Great Proletarian Cultural Revolution in a last attempt to remake China in his image. He believed that the country was led by a party infested from the top on down with “capitalist-roaders” who had betrayed the proletarian goals of true socialism by following the bourgeois line. Denied support in the power structure, Mao sought help from the outside, mobilizing millions of high school and college students as the “Red Guards” to strike down his enemy in an unprecedented campaign that left the nation nearly paralyzed. Red Guard organizations of confusing ideological persuasions soon proliferated throughout the country, and the whole movement quickly got out of control and degenerated into total chaos. That the Red Guards were used by Mao as a tool in the ideologically based power struggle within the party is not only the consensus of most observers but also has been freely admitted by many former Red Guards. © 1988 by Taylor & Francis. All rights reserved.
Journal Abbreviation: Hum. Rights in the People's Repub. of China
Keywords: dept.his

Red guards and political dissidents (II): Victims beyond a generation - Lee, T.-L. (Hum. Rights in the People's Repub. of China, 2019)
Many former Red Guards who through the Cultural Revolution were encouraged to participate in unrestrained violence, saw the seamy side of the regime as a result and were themselves eventually suppressed and reached the conclusion that the system was corrupt and had to be changed. Former Red Guards who turned political activists varied greatly in their often vaguely defined outlooks and their intensity of commitment and activity. Wei Jingsheng, China’s most celebrated Red Guard-turned dissident, related a similar experience in an unfinished autobiographical account written before his arrest and smuggled out of the country in 1980. Many former Red Guards understandably see a silver lining in the destructive rampage they committed during the height of the Cultural Revolution. The Red Guard movement has come full circle. The human rights tragedy of the movement is threefold. In the first stage, the Red Guards were Mao’s “little generals” trampling on the human rights of their victims. © 1988 by Taylor & Francis. All rights reserved.
Journal Abbreviation: Hum. Rights in the People's Repub. of China
Keywords: dept.his

Prime (and crime) time: Boxing in the 1950s - Rondinone, T. (The Camb. Companion to Box., 2019)
Journal Abbreviation: The Camb. Companion to Box.
Keywords: dept.his

Human rights in the people’s republic of China - Wu, Y.-L.; Michael, F.; Copper, J.F.; Lee, T.-L.; Chang, M.H.; Gregor, A.J. (Taylor and Francis, 2019)
This book examines the effects that political institutions, the legal system, and economic policies have had on the human rights record in the PRC since 1949. The authors first address the problems of assessing political liberties in a nation that emphasizes economic over civil rights and that has traditionally valued collective rights over individ. © 1988 by Taylor & Francis. All rights reserved.
Journal Abbreviation: Hum. Rights in the People's Repub. of China Pages: 332 Publication Title: Hum. Rights in the People's Repub. of China
Keywords: dept.his

The Folklore of Deinstitutionalization: Popular Film and the Death of the Asylum, 1973–1979 - Rondinone, Troy (Journal of American Studies, 2019)
The demise of America's state mental hospital system, or “deinstitutionalization,” has received much attention from sociologists and historians of medicine. Less understood is the manner in which the public experienced and came to terms with it. Using elements of folklore and horror studies, I will examine how popular films accommodated audiences to institutional decline and confirmed popular antistatist pessimism. The Exorcist (1973), One Flew over the Cuckoo's Nest (1975), Halloween (1978), and When a Stranger Calls (1979) helped weave a tapestry of distrust. By endorsing popular conceptions of institutional failure and presenting mythical narratives of individualist triumph, these films helped pave a path towards the conservative Reagan era to come.
1 citations (Crossref) [2023-10-31]
Keywords: dept.his; peer-reviewed

Lovecraft Meets the Mummy: Orientalism, Race, and Monstrous Egypt in “Imprisoned with the haraohs” and “Out of the Aeons” - Rondinone, Troy (Lovecraftian Proceedings No. 3., 2019)
OCLC: 1112383993
Keywords: dept.his; faculty_collection

The unforgettable age: young in Costa Rica of XX century - Coury Kordick, Carmen Coury (Americas, 2019)
0 citations (Crossref) [2023-10-31] tex.address: 32 AVENUE OF THE AMERICAS, NEW YORK, NY 10013-2473 USA tex.affiliation: Kordick, C (Reprint Author), Southern Connecticut State Univ, New Haven, CT 06515 USA. Kordick, Carmen, Southern Connecticut State Univ, New Haven, CT 06515 USA. tex.author-email: carmen.kordick@gmail.com tex.da: 2019-10-31 tex.doc-delivery-number: JB8QB tex.eissn: 1533-6247 tex.journal-iso: Americas tex.number-of-cited-references: 1 tex.publisher: CAMBRIDGE UNIV PRESS tex.research-areas: History tex.times-cited: 0 tex.type: Book review tex.unique-id: ISI:000488837000030 tex.usage-count-last-180-days: 0 tex.usage-count-since-2013: 0 tex.web-of-science-categories: History
Keywords: dept.his; peer-reviewed

Contesting the Origins of the First World War: An Historiographical Argument - Paddock, Troy R. E. (Routledge, 2019)
Contesting the Origins of the First World War challenges the Anglophone emphasis on Germany as bearing the primary responsibility in causing the conflict and instead builds upon new perspectives to reconsider the roles of the other Great Powers. Using the work of Terrance Zuber, Sean McMeekin, and Stefan Schmidt as building blocks, this book reassesses the origins of the First World War and offers an explanation as to why this reassessment did not come about earlier. Troy R.E. Paddock argues that historians need to redraw the historiographical map that has charted the origins of the war. His analysis creates a more balanced view of German actions by also noting the actions and inaction of other nations. Recent works about the roles of the five Great Powers involved in the events leading up to the war are considered, and Paddock concludes that Germany does not bear the primary responsibility. This book provides a unique historiographical analysis of key texts published on the origins of the First World War, and its narrative encourages students to engage with and challenge historical perspectives.
Keywords: dept.his

‘Mixt marriages’: Ethnic and religious intermarriage among German-speakers in eighteenth-century Pennsylvania - McDaniel, Marie Basile (The History of the Family, 2019)
Civil and religious authorities in eighteenth-century America grew increasingly concerned over the freedom with which young people chose their marriage partners. Correlating racial, religious and cultural similarity in marriage to a stable society, these authorities attempted to limit marriage and sexual choices by requiring parental authority for marriage, distributing permits to a select few to perform marriages, and criminalizing racial miscegenation. Eighteenth-century Pennsylvania German authorities supported this attitude because they associated ethnic and religious out-marriage with the weakening of the body and the destruction of society. My study uses the marriage and birth records of eighteenth-century Pennsylvania Germans to examine their marriage and sexual relationships. I discovered that Pennsylvania Germans overwhelmingly chose to marry other German-speakers, out of proportion with their population. By examining the then available works on marriage and procreation, I discovered that Pennsylvania Germans read works that emphasized the necessity and importance of intra-ethnic and religious sex and marriage for the health of their children. Pennsylvania Germans chose their marriage partners in alignment with their community’s attitudes towards those of other ethnicities and religions. A small data set further suggests that relationships with non-Germans occurred but rarely became formalized. This complicates what we know about the sexual and emotional revolutions in the seventeenth and eighteenth centuries; far from a linear progression of attitudes towards sex, marriage, and others, eighteenth-century Pennsylvania Germans expressed multiple, contextually-driven perspectives, and in the process they created and maintained strong ethnic communities. © 2019, © 2019 Informa UK Limited, trading as Taylor & Francis Group.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/003-122-575-243-949, pop00292 tex.type: [object Object]
Keywords: Defoe; German (citizen); German-speakers; Marriage; Pennsylvania; article; child; colonial; dept.his; destruction; ethnicity; female; human; human experiment; male; marriage; peer-reviewed; pre-marital; religion

Roman exempla in the early Tudor period - Kern, Darcy (English: Journal of the English Association, 2019)
Abstract. Roman exempla, or moralizing anecdotes, appear frequently in the English literature of the early Tudor period. Textual, authorial, and historical exe
0 citations (Crossref) [2023-10-31]
Keywords: dept.his; peer-reviewed

Empire by invitation: William Walker and manifest destiny in Central America - Coury Kordick, Carmen (Americas, 2019)
1 citations (Crossref) [2023-10-31] tex.address: 32 AVENUE OF THE AMERICAS, NEW YORK, NY 10013-2473 USA tex.affiliation: Kordick, C (Reprint Author), Southern Connecticut State Univ, New Haven, CT 06515 USA. Kordick, Carmen, Southern Connecticut State Univ, New Haven, CT 06515 USA. tex.author-email: carmen.kordick@gmail.com tex.da: 2019-10-31 tex.doc-delivery-number: HQ9TB tex.eissn: 1533-6247 tex.journal-iso: Americas tex.number-of-cited-references: 1 tex.publisher: CAMBRIDGE UNIV PRESS tex.research-areas: History tex.times-cited: 0 tex.type: Book review tex.unique-id: ISI:000462769300017 tex.usage-count-last-180-days: 0 tex.usage-count-since-2013: 0 tex.web-of-science-categories: History
Keywords: book.review; dept.his; peer-reviewed

Book Review: Viet Nam: A history from earliest times to the present. - Thompson, C. Michele (Journal of Asian Studies, 2019)
0 citations (Crossref) [2023-10-31] tex.eissn: 1752-0401 tex.unique-id: ISI:000461085900040
Keywords: book.review; dept.his

Boxing in the ancient world - Nakamura, Byron J. (The Cambridge Companion to Boxing, 2019)
Keywords: dept.his

The real anticommunism. Politics, gender and Cold War in Costa Rica (1948-1973) - Coury Kordick, Carmen (Americas, 2019)
0 citations (Crossref) [2023-10-31] tex.eissn: 1533-6247 tex.unique-id: ISI:000458113400039
Keywords: book.review; dept.his; peer-reviewed

A biography of a map in motion: Augustine Herrman's Chesapeake. - Petto, Christine M. (Journal of British Studies, 2019)
0 citations (Crossref) [2023-10-31] tex.eissn: 1545-6986 tex.unique-id: ISI:000462676000018
Keywords: book.review; dept.his

Beyond borders: Jean Gerson’s conciliarism in fifteenth-century Spain - Kern, Darcy (Renaissance and Reformation, 2019)
In recent years there has been renewed interest in conciliarism, the belief that the authority of the universal church resides in an ecumenical council, not the pope, though the perception remains that conciliarism had a negligible impact in Iberia. One way to better understand the evolution of conciliar thought in the Spanish kingdoms is by looking at the circulation of the works and ideas of the French conciliarist Jean Gerson (1363–1429). Though a complete reconstruction of Gerson’s circulation is impossible, one can offer an initial overview of his impact in the Spanish kingdoms not simply by counting manuscripts or incunabula, as valuable as that is, but by thinking broadly about networks of exchange and dissemination. Gerson’s works came to Spain through the church councils, trans-Pyrenees Carthusian networks, monastic reformers, printers and printing houses, mendicant reformers, and the library of the University of Salamanca. © 2019, (publisher Name). All Rights Reserved.
1 citations (Crossref) [2023-10-31]
Keywords: dept.his; peer-reviewed

Rolf Brandt and a conservative literary journalism - Paddock, Troy RE (Literary Journalism Studies, 2019)
Rolf Brandt (1886-1953) was a German journalist, author, and political commentator. His first work was as a war reporter on the Eastern Front during the opening months of the Great War (World War I). His reports appeared in several important German newspapers (Norddeutsche Allgemeine Zeitung and Frankfurter Zeitung) and were compiled and published in 1915 as Fünf Monate an der Ostfront: Kriegsberichte (Five months on the Eastern Front: War reports). Brandt's reports were more than just army-approved press releases. He wrote in a way that constructed a bridge between the home front and the front lines. In the process he employed techniques now associated with literary journalism. With a clear point of view, he told his story through a sequence of scenes, instead of a simple historical narrative, and included genuine dialogue and status details. While scholars of German literary journalism point to Egon Erwin Kisch as the originator of German literary journalism, this study suggests Brandt should be considered an early practitioner of literary journalism in the German language. More interestingly, Brandt's particular brand of literary journalism had an unmistakably conservative nationalist perspective, thus suggesting that it is possible to have a conservative form of literary journalism. © 2019 Literary Journalism Studies. All Rights Reserved.
Keywords: Conservative literary journalism; Germany; Propaganda; Rolf Brandt; Russia; World War I; dept.his; peer-reviewed; ⛔ No DOI found